METHOD OF ACQUIRING HIGH QUALITY SURFACE TURBULENT FLUXES OVER THE LOESS PLATEAU. Issue 4 (July 2016) - Guang‐Hui, YUAN; Lei, ZHANG; Yao, LI; Jie‐Ning, LIANG
Abstract: To analyze the applicability of double rotation (DR), planar fit (PF) and fetch planar fit (FPF) over complicated terrain, turbulent data from the Semi‐Arid Climate and Environment Observatory of Lanzhou University (SACOL) are used. A parameterization scheme is provided in integral turbulent characteristics (ITC) test for SACOL data. The overall quality after data processing and quality control including sonic temperature correction, coordinate rotations, WPL correction (correction for density fluctuations), stationarity test and ITC test shows that about 45%∼62% of the total data are of high quality for friction velocity ( u * ), 66%∼68% for sensible heat flux, 62%∼65% for latent heat flux and 52%∼54% for CO2 flux. The proportion of the high quality of u * obtained by DR is 17% higher than PF, while the proportion of high quality data of the latter three kinds of fluxes obtained by PF is 2%∼3% higher than DR. The differences between PF and FPF are mainly in u * . Comparing the three coordinate rotations in the dominant wind direction, DR still obtains the best quality of u * . The use of DR is recommended in the complicated terrain for reducing calculation and improving the data quality.